2003
DOI: 10.1126/science.1085167
|View full text |Cite
|
Sign up to set email alerts
|

A Targeting Motif Involved in Sodium Channel Clustering at the Axonal Initial Segment

Abstract: The sorting of sodium channels to axons and the formation of clusters are of primary importance for neuronal electrogenesis. Here, we showed that the cytoplasmic loop connecting domains II and III of the Na v 1 subunit contains a determinant conferring compartmentalization in the axonal initial segment of rat hippocampal neurons. Expression of a soluble Na v 1.2II-III linker protein led to the disorganization of endogenous sodium channels. The motif was sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
375
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 328 publications
(392 citation statements)
references
References 28 publications
15
375
2
Order By: Relevance
“…Clustering of signaling proteins is an intriguing phenomenon of cell biology (42,43). Our present study revealed that clustering of RyRCs into arrays endows interacting channels with unique properties.…”
Section: Discussionmentioning
confidence: 87%
“…Clustering of signaling proteins is an intriguing phenomenon of cell biology (42,43). Our present study revealed that clustering of RyRCs into arrays endows interacting channels with unique properties.…”
Section: Discussionmentioning
confidence: 87%
“…However, the most parsimonious interpretation of the data considered together is that Na v 1.5 associates with ankyrin-G and that ankyrin-G is required for cell surface expression of Na v 1.5 in cardiomyocytes. The ankyrin-G-binding motif (VPIAXX-ESD) is conserved among Na v 1.1, 1.2, 1.4, 1.5, and 1.6, and also is required for Na v channel targeting in both neurons (7,8). Therefore, an ankyrin-G-based mechanism for Na v channel targeting appears a conserved feature of both cardiomyocytes and neurons.…”
Section: Discussionmentioning
confidence: 99%
“…6,19,27 Accommodation between different days could be viewed as a form of activitydependent functional plasticity of the peripheral nervous system. As demonstrated by Debanne et al, 8 the axon should not only be considered as a simple structure that reliably transmits the action potential from the cell body to the nerve terminal: it is also able to express nonsynaptic mechanisms of plasticity, which range from activation and inactivation 7 to dynamic compartmentalization 15,16 of ionic channels. This nonsynaptic form of plasticity could underlie the variability in TF that we observed between different days (mainly between the first day and the subsequent 2 days) and should always be considered in the planning of experimental protocols with serial measurements on the same subject.…”
Section: Cramp and Fasciculation Induction By Transcutaneousmentioning
confidence: 99%